Epidemiological patterns of cervical human papillomavirus infection among women presenting for cervical cancer screening in North-Eastern Nigeria (2015)
Background: Sub-Saharan countries including Nigeria have the highest burden of Human Papillomavirus (HPV) infection in the world. Most studies on HPV surveillance in Nigeria were done in the southern part of the country. Geographical and socio-cultural diversity of Nigeria makes these data unlikely to be universally representative for the entire country. Northern Nigeria especially the North-East carries a higher prevalence of cervical cancer and many of its risk factors. The region may be harbouring a higher prevalence of HPV infection with a possibility of different genotypic distribution. This study was carried out to determine the burden and confirm the predominant HPV genotypes among women presenting for cervical cancer screening at the Federal Teaching Hospital Gombe (FTHG), North-eastern, Nigeria. Methods: The study was an observational hospital based cross sectional study among women who presented for cervical cancer screening in FTHG. A total of 209 consenting women were tested for cervical HPV infection using PCR. DNA sequencing was carried out on positive samples to determine the prevalent HPV genotypes. Results: The prevalence of cervical HPV infection among the participants with mean age of 39.6 ± 10.4 years was 48.1 %. The five most predominant genotypes were 18, 16, 33, 31 and 35, with prevalence of 44.7 %, 13.2 %, 7.9 %, 5.3 % and 5.3 % respectively. Other genotypes observed were 38, 45, 56, 58, 82 and KC5. Multiple HPV infections were detected among 7.9 % of participants. Risk factors such as level of education (X2 = 15.897; p = 0.007), age at sexual debut (X2 = 6.916; p = 0.009), parity (X2 = 23.767; p = 0.000), number of life time sexual partners (X2 = 7.805; p = 0.005), age at first pregnancy (X2 = 10.554; p = 0.005) and history of other malignancies (X2 = 7.325; p = 0.007) were found to have a statistically significant association with HPV infection. Conclusion: This study identified a high burden of HPV infection in Northern Nigeria while also confirming HPV 18 and 16 as the most predominant genotypes. It further justifies the potential benefit of the currently available HPV vaccines in the area. A larger and community based study is however recommended for better representation of the area.